2008
DOI: 10.1299/jmtl.1.170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Visual Cues and Quantification of Drivers' Perception of Proximity Risk to the Lead Vehicle in Car-Following Situations

Abstract: Longitudinal vehicle control and/or warning technologies that operate in accordance with drivers' subjective perception of risk need to be developed for driver-support systems, if such systems are to be used fully to achieve safer, more comfortable driving. In order to accomplish this goal, it is necessary to identify the visual cues utilized by drivers in their perception of risk when closing on the vehicle ahead in a car-following situation. It is also necessary to quantify the relation between the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 3 publications
(3 reference statements)
0
47
0
3
Order By: Relevance
“…Inverse tau is a visually available estimate of inverse TTC (Lee, 1976), and thus increases as the potential collision draws nearer. Furthermore, it has often been suggested that inverse tau and similar quantities play an important role in determining drivers' responses to obstacles and collision threats (Lee, 1976;Kiefer et al, 2003Kiefer et al, , 2005Fajen, 2005Fajen, , 2008Kondoh et al, 2008Kondoh et al, , 2014Jurecki & Stanczyk, 2009, 2014.…”
Section: Analyses Of Kinematics-dependencementioning
confidence: 99%
“…Inverse tau is a visually available estimate of inverse TTC (Lee, 1976), and thus increases as the potential collision draws nearer. Furthermore, it has often been suggested that inverse tau and similar quantities play an important role in determining drivers' responses to obstacles and collision threats (Lee, 1976;Kiefer et al, 2003Kiefer et al, , 2005Fajen, 2005Fajen, , 2008Kondoh et al, 2008Kondoh et al, , 2014Jurecki & Stanczyk, 2009, 2014.…”
Section: Analyses Of Kinematics-dependencementioning
confidence: 99%
“…Research has shown that headway from the lead vehicle (Green, 2004), time to collision (Kondoh et al, 2007;Wada et al, 2010), and variation of speed (Cacciabue, 2007) are key factors examined for primary task demand relating to traffic. Although the aim of the study is to explore driver's temporal workload in response to changes in immediate traffic, understanding possible adaptation in driving behaviour may provide clarification of changes in driver workload and thus verify the utility of subjective measures in quantifying these external demands.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Fixed-threshold: The automated driving system performs a lane change if the value of "Risk Perception" [12] is less than the fixed-threshold, where Risk Perception is a linear combination of inverse TTC (time to collision) and inverse THW (time headway). It is known that the value of Risk Perception is strongly related to the human's feeling of risk on rear-end collision [12].…”
Section: Automatic Lane-changementioning
confidence: 99%
“…It is known that the value of Risk Perception is strongly related to the human's feeling of risk on rear-end collision [12]. The threshold value is set at 1.35 in this experiment.…”
Section: Automatic Lane-changementioning
confidence: 99%